2009
DOI: 10.1007/s12160-009-9092-9
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Quality of Life in ALS Patients and Caregivers

Abstract: Low QOL among ALS patients is likely due to pre-existing individual differences, whereas both individual differences such as demographics (e.g., age) and disease progression are likely to affect QOL among caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
46
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 55 publications
(68 reference statements)
11
46
1
Order By: Relevance
“…Our findings are in line with those reported by Cohen et al 42 in subjects with terminal illness, where improvement in HRQOL went beyond symptom control following admission to a palliative care unit, and with findings from Roach et al 43 in subjects with amyotrophic lateral sclerosis, suggesting that in subjects under critical conditions, life goals, hopes, and expectations are similarly independent from the diseases. In general, the current uncontrolled study confirms that long-stay ICU survivors tend to improve their HRQOL, as reported previously by other authors in compromised subjects with different pathologies.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with those reported by Cohen et al 42 in subjects with terminal illness, where improvement in HRQOL went beyond symptom control following admission to a palliative care unit, and with findings from Roach et al 43 in subjects with amyotrophic lateral sclerosis, suggesting that in subjects under critical conditions, life goals, hopes, and expectations are similarly independent from the diseases. In general, the current uncontrolled study confirms that long-stay ICU survivors tend to improve their HRQOL, as reported previously by other authors in compromised subjects with different pathologies.…”
Section: Discussionsupporting
confidence: 93%
“…Ambivalence over emotional expression, social constraints, and low emotional approach coping were all related to lower psychological well-being across the course of the study (e.g., Roach et al, 2009). However, ambivalence over emotional expression was also related to a more robust response to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Amyotrophic Lateral Sclerosis (ALS) evokes a number of issues related to psychological adaptation, such as adjustment to changes in functional abilities and physical appearance, guilt about being burdensome to caregivers, loss of autonomy, and coping with the certainty of death. However, there has been a paucity of research examining the psychological aspects of this disease, and, to date, few studies have incorporated a psychological intervention for people with ALS (Hunter, Robinson, & Neilson, 1993; Sebring & Moglia, 1987), despite the suggestion that the quality of life of people with ALS is more determined by psychological and existential factors than by physical health (e.g., Roach, Averill, Segerstrom, & Kasarskis, 2009; Robbins, Simmons, Bremer, Walsh, & Fischer, 2001; Simmons, Bremer, Robbins, Walsh, & Fischer, 2000). People with ALS differ from other patient groups for whom expressive disclosure has been used as an intervention (e.g., cancer, rheumatoid arthritis, asthma) in a number of important ways, including faster disease progression, paralysis, loss of independence, inability to communicate, and universal fatality as a prognosis.…”
mentioning
confidence: 99%
“…As the disease progresses, strain on and psychological distress of informal caregivers of patients with ALS increase significantly,2–4 while caregivers’ quality of life worsens 5. Role strain due to many demands because of managing care, providing care, supporting the patient in decision-making, patient advocating and ordinary daily live responsibilities may have an impact on caregiver strain 6 7…”
Section: Introductionmentioning
confidence: 99%